DUKUNGAN PASTORAL KONSELING MELALUI MUBAWAKI: MEMBANGUN EMPATI DAN SOLIDARITAS - Okdita Katiandagho; Sylvia Evangelin Bawihu; Geby Ladesya Kalensang (TENTIRO: Jurnal Pendidikan dan Kesehatan, 2024)
Local wisdom places more emphasis on the place and locality of the wisdom so that it does not have to be wisdom that has been passed down from generation to generation. Meanwhile, Siau has a variety of local wisdom, both long-standing local wisdom that has been passed down from generation to generation, as well as new or recent local wisdom that has emerged as a result of interactions with other communities and cultures, one of which is mubawaki. Mubawaki is one of the local wisdoms where the people have a very high level of empathy and solidarity from the Siau people in the context of bereaved people, they work together to help the bereaved families, starting from the fathers who make tents and the mothers who help in kitchen and food delivery. The aim of this research is to see how pastoral counseling supports in mubawaki